2011
DOI: 10.1111/j.1574-6941.2011.01101.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of hydrogen and acetate on benzene mineralisation under sulphate-reducing conditions

Abstract: Syntrophic mineralisation of benzene, as recently proposed for a sulphatereducing enrichment culture, was tested in product inhibition experiments with acetate and hydrogen, both putative intermediates of anaerobic benzene fermentation. Using [ 13 C 6 ]-benzene enabled tracking the inhibition of benzene mineralisation sensitively by analysis of 13 CO 2 . In noninhibited cultures, hydrogen was detected at partial pressures of 2.4 Â 10 À6 AE 1.5 Â 10 À6 atm. Acetate was detected at concentrations of 17 AE 2 mM. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
19
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 39 publications
4
19
0
Order By: Relevance
“…A comparison of the degradation and formation rates revealed that around 90% of the carbon of 13 C-benzene was degraded to 13 CO 2 . This agrees with previous findings, where also 87-95% of carbon derived from benzene was converted to CO 2 (Herrmann et al, 2010;Rakoczy et al, 2011):…”
Section: Cultivationsupporting
confidence: 93%
See 3 more Smart Citations
“…A comparison of the degradation and formation rates revealed that around 90% of the carbon of 13 C-benzene was degraded to 13 CO 2 . This agrees with previous findings, where also 87-95% of carbon derived from benzene was converted to CO 2 (Herrmann et al, 2010;Rakoczy et al, 2011):…”
Section: Cultivationsupporting
confidence: 93%
“…Acetyl-CoA is then either further degraded to CO 2 or released as acetate by the Clostridiales, depending on the energy level. Deltaproteobacteria further metabolized the putatively released acetate, and interspecies hydrogen transfer possibly takes place between Clostridiales and Deltaproteobacteria as suggested previously (Rakoczy et al, 2011). Our study illustrates the power of protein-based SIP, in combination with a comprehensive metagenome data set, to decipher the carbon flow within complex microbial communities.…”
Section: Community Overviewsupporting
confidence: 75%
See 2 more Smart Citations
“…The biodegradation of ethanol led to the formation and accumulation of acetate (Figure 1). Although not toxic, the presence of acetate as low as 0.3 mM (Rakoczy et al, 2011) could hinder the thermodynamic feasibility of BTEX degradation by syntrophic microorganisms typically associated with sulfate-reducing and methanogenic conditions (Ulrich and Edwards, 2003). Benzene and toluene degradation in our column experiments only occurred after the onset of acetate removal (Figure 1).…”
Section: Resultsmentioning
confidence: 96%